Gene transfer between fungal species triggers repeated coffee wilt disease outbreaks. - Brenda D Wingfield; Michael J Wingfield (PLoS Biology)
Two outbreaks of coffee wilt disease have devastated African coffee production. A PLOS Biology study suggests that horizontal gene transfer via large Starship transposons between 2 fungal species played a key role in the repeated emergence of the disease.